Three-and-a-half to 18 year outcome data for costal osteochondral grafts for salvage of the proximal pole of the scaphoid. (November 2020) - Bain, Charles; Tham, Stephen; Powell, Chris; Berger, Anthony; Withers, Aaron; McCombe, David
Twelve patients who had undergone costal osteochondral graft reconstruction of the proximal pole of scaphoid were evaluated with clinical examination, patient-reported outcome scores and radiographs with an average follow-up of 10 years (range 3.5–18). The range of wrist motion was not significantly changed compared with the preoperative range of motion and functional outcomes scores were acceptable. The patients reported low pain scores despite the universal presence of radiographic changes of reduced carpal height and arthritis of the midcarpal and radiocarpal joints. Costal osteochondral graft reconstruction of the proximal pole of scaphoid offers good long-term pain relief and function. Level of evidence: IV